2014
DOI: 10.1088/0004-637x/785/2/83
|View full text |Cite
|
Sign up to set email alerts
|

The Banana Project. V. Misaligned and Precessing Stellar Rotation Axes in Cv Velorum

Abstract: As part of the Binaries Are Not Always Neatly Aligned project (BANANA), we have found that the eclipsing binary CV Velorum has misaligned rotation axes. Based on our analysis of the Rossiter-McLaughlin effect, we find sky-projected spin-orbit angles of β p = −52• ± 6 • and β s = 3 • ± 7• for the primary and secondary stars (B2.5V + B2.5V, P = 6.9 days). We combine this information with several measurements of changing projected stellar rotation speeds (v sin i ) over the last 30 yr, leading to a model in which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…We anticipate that more detailed studies of (subsamples of) the Kepler EB sample will further constrain tidal circularization theory. We also expect our findings to be of interest in the context of tidal theory for stellar obliquities in double star systems (e.g., Albrecht et al 2014) and in exoplanet systems (e.g., Winn et al 2010;Albrecht et al 2012).…”
Section: Discussionmentioning
confidence: 78%
“…We anticipate that more detailed studies of (subsamples of) the Kepler EB sample will further constrain tidal circularization theory. We also expect our findings to be of interest in the context of tidal theory for stellar obliquities in double star systems (e.g., Albrecht et al 2014) and in exoplanet systems (e.g., Winn et al 2010;Albrecht et al 2012).…”
Section: Discussionmentioning
confidence: 78%
“…Some binary stars possess rotation spins inclined with respect to their orbital spin (e.g. Albrecht et al 2009;Zhou & Huang 2013;Albrecht et al 2014) and may reflect the same processes that lead to inclined discs. Proto-binaries formed by fragmentation must have an initial separation larger than 10 AU, with typical separations larger than 100 AU (Bate 2012).…”
Section: Observational and Theoretical Evidence Of Mutually Inclined mentioning
confidence: 99%
“…We also aim to revisit the relative frequencies of low-mass stars to planets, to brown dwarfs in order to confirm the presence, extent and dryness of the brown dwarf desert (Marcy & Butler 2000;Grether & Lineweaver 2006;Sahlmann et al 2011;Ma & Ge 2014). We will compare the stellar and planetary eccentricity/period and eccentricity/mass distributions in order to study tides (Zahn & Bouchet 1989;Mathieu et al 1990;Mazeh et al 1997;Terquem et al 1998;Meibom & Mathieu 2005;Milliman et al 2014), investigate whether the statistics on the presence of additional perturbing bodies are similar (Tokovinin et al 2006;Knutson et al 2014;Neveu-VanMalle et al 2016), and find out if the spinorbit misalignments frequently observed in hot Jupiter systems are also observed in binary stars thanks to the RossiterMcLaughlin effect (Hale 1994;Triaud et al 2010;Albrecht et al 2014;Esposito et al 2014;Lendl et al 2014;Winn & Fabrycky 2015).…”
Section: Introductionmentioning
confidence: 99%